Energetic prediction on the stability of A2Mg12Si7, A2Mg4Si3, and AMgSi in the A2Si–Mg2Si system (A=Ca, Sr and Ba) and their calculated electronic structures - Imai, Yoji; Mori, Yoshihisa; Nakamura, Shigeyuki; Takarabe, Ken-ichi (Journal of alloys and compounds, 2014)
•Formation energies of A2Mg4Si3, A2Mg12Si7, and AMgSi (A=Ca,Sr,Ba) were calculated.•All AMgSi are quite stable compared to mixture of A2Si and Mg2Si.•Ba2Mg4Si3 and Sr2Mg4Si3 are predicted to be stable, but Ca2Mg4Si3 is not.•Ca2Mg12Si7 and Sr2Mg12Si7 are energetically unstable.•Stability of Ba2Mg12Si7 is a tender subject. In order to evaluate the relative stability of A2Mg4Si3, A2Mg12Si7, and AMgSi (A=Ca, Sr, and Ba) in the A2Si–Mg2Si system, electronic energy changes in the formation of these compounds were calculated using a density-functional theory with the Perdew–Wang generalized gradient approximations. It was found that (1) AMgSi’s are quite stable compared to equi-molar mixture of A2Si and Mg2Si, (2) Ba2Mg4Si3 and Sr2Mg4Si3 are also stable, (3) Ca2Mg4Si3 and Ca2Mg12Si7 are less stable than the mixture of CaMgSi and Mg2Si, and (4) Stability of Ba2Mg12Si7 is a tender subject and Sr2Mg12Si7 is energetically unstable compared to the mixture of Sr2Mg4Si3 (or, SrMgSi) and Mg2Si. The presence of Sr2Mg12Si7 may be due to the vibrational and/or configurational entropy, which are not treated in the present study. From the calculated electronic densities of state, complex compounds of SrMgSi and Mg2Si have both p-type and n-type character, depending on the ratio of SrMgSi and Mg2Si in that compound.